Bixa Orellana L Leaf infusion as an Anti-inflammatory Agent in Carrageenan-induced Wistar Rats - Yusuf, Sabrina Munggarani; Rohmawaty, Enny; Nusjirwan, Rama (Althea Medical Journal, 2014)
Background: One of the characteristics of inflammation is swelling or edema. Inflammation can be treated with traditional medicine, such as Bixa orellana L. Bixa orellana L leafÂ contains flavonoid and tannin responsible for its anti-inflammatory effect. This study was conducted to analyse the ability of Bixa orellana L leaf infusion (BOLI) to suppress paw edema in carrageenan-induced Wistar rats.Methods: This study was conducted in the Animal Laboratory of Department of Pharmacology and Therapy Faculty of Medicine Universitas Padjadjaran in October 2012. Bixa orellana L leaves were procured from Lembang, Bandung, and were botanically identified at the Herbarium of Universitas Padjadjaran, Jatinangor. Thirty female Wistar rats were randomly divided into five groups. Group 1 was given 5 mL aquades as a control, three groups received BOLI with 0,09 g; 0,18 g; and 0,36 g dosage respectively; and group 5 was given 0,9 mg diclofenac. At 1 hour after treatment, all rats were induced by carrageenan injection subcutaneously. Paw edema changes were quantified at 0, 1, 2, 3, 4, 5, 6, and 24 hour afterwards. Data were analysed using Kruskal-Wallis and Mann-Whitney testResults: Based on paw edema inhibition percentage, 0.18 g of BOLI was shown most effective (16.97%) compared to 0.09 g (10.96%) and 0.36 g (7.50%). Interestingly, no significant differences of anti-inflammatory effect were observed between groups that were treated with 0,18 g of BOLI and diclofenac (p > 0,005).Conclusions: The BOLI can suppress inflammation comparable to diclofenac. The effective dosage is 0.18 g/200 g BW/day.[AMJ.2014;1(1):7â12]Keywords: anti-inflammatory, Bixa orellana L leaf, paw edemaÂ Infusa Daun Kesumba (Bixa Orellana L) sebagai Anti Inflamasi pada Tikus Wistar yang Diinduksi CarrageenanÂ Latar Belakang: Salah satu ciri khas dari peradangan atau inflamasi adalah adanya pembengkakan atau edema. Peradangan dapat diobatiÂ dengan obat tradisional, seperti Kesumba (Bixa orellana). Daun Kesumba diketahui mengandung flavonoid dan tanin yang berfungsi sebagai anti-inflamasi. Penelitian ini dilakukan untuk menganalisis kemampuan infusa daun kesumba (Bixa orellana) (BOLI) dalam mengurangi edema tungkai pada kaki tikus Wistar yang diinduksi Carrageenan.Metode: Penelitian ini dilakukan di Laboratorium Hewan Departemen Farmakologi dan Terapi di Rumah Sakit Umum Dr. Hasan Sadikin Bandung pada bulan Oktober 2012. Daun Kesumba (Bixa Orellana) diperoleh dari Lembang, Bandung, dan diidentifikasi botani di Herbarium Universitas Padjadjaran, Jatinangor. Tiga puluh tikus Wistar betina secara acak dibagi menjadi lima kelompok. Kelompok kontrol negatif diberi 5 mL aquades, tiga kelompok menerima BOLI dengan 0,09 g; 0,18 g; dan masing-masing 0,36 g dosis; sedangkan kelompok kontrol positif diberikan 0,9 mg diklofenak. Pada 1 jam setelah pengobatan, semua tikus diinduksi oleh subkutan injeksi karagenan. Perubahan edema (Paw) yang diukur pada 0, 1, 2, 3, 4, 5, 6, dan 24 jam sesudahnya. Data dianalisis denganmenggunakanKruskal-Wallis dan uji Mann-Whitney.Hasil: Berdasarkan persentase pengurangan edema tungkai, kelompok 0,18g BOLI terlihat paling efektif (16,9%) dibandingkan dengan 0,09 g (10,9%) dan 0,36 g (7,5%). Tidak ada perbedaan yang signifikan dari efek anti-inflamasi yang diamati antara kelompok-kelompok yang diobati dengan 0,18 g BOLI dan diklofenak (p> 0.005).Simpulan: Infusa Daun Kesumba (Bixaorellana) dapat menekan peradangan sama baiknya dengan diklofenak. Dosis efektif adalah 0,18 g /200 g BB / hari.Kata kunci: anti-inflamasi, daun kesumba (Bixaorellana), edema tungkaiÂ DOI: 10.15850/amj.v1n2.347